Raffinose degradation-related gene GhAGAL3 was screened out responding to salinity stress through expression patterns of GhAGALs family genes - Chen, Wenhua; Cui, Yupeng; He, Yunxin; Zhao, Lanjie; Cui, Ruifeng; Liu, Xiaoyu; Huang, Hui; Zhang, Yuexin; Fan, Yapeng; Feng, Xixian; Ni, Kesong; Jiang, Tiantian; et al. (Frontiers in Plant Science, 2023)
A-galactosidases (AGALs), the oligosaccharides (RFOs) catabolic genes of the Raffinose family, play crucial roles in plant growth and development and in adversity stress. They can break down the nonreducing terminal galactose residues of glycolipids and sugar chains. In this study, the whole genome of AGALs was analyzed. Bioinformatics analysis was conducted to analyze members of the AGAL family in Gossypium hirsutum, Gossypium arboreum, Gossypium barbadense, and Gossypium raimondii. Meanwhile, RT-qPCR was carried out to analyze the expression patterns of AGAL family members in different tissues of terrestrial cotton. It was found that a series of environmental factors stimulated the expression of GhAGAL3 gene. The function of GhAGAL3 was verified through virusinduced gene silencing (VIGS). As a result, GhAGAL3 gene silencing resulted in milder wilting of seedlings than the controls, and a significant increase in the raffinose content in cotton, indicating that GhAGAL3 responded to NaCl stress. The increase in raffinose content improved the tolerance of cotton.Findings in this study lay an important foundation for further research on the role of GhAGAL3 gene family in the molecular mechanism of abiotic stress resistance in cotton.